2016
DOI: 10.1016/j.crvi.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Population structure and marker–trait association of salt tolerance in barley (Hordeum vulgare L.)

Abstract: Association mapping is becoming an important tool for identifying alleles and loci responsible for dissecting highly complex traits in barley. This study describes the population structure and marker-trait association using general linear model (GLM) analysis on a site of 60 barley genotypes, evaluated in six salinity environments. Ninety-eight SSR and SNP alleles were employed for the construction of a framework genetic map. The genetic structure analysis of the collection turned out to consist of two major s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…The diverse set consisted of 60 spring barley genotypes. The biological status, pedigree information, and population structure have been illustrated [ 90 ]. The list of all genotypes is presented in Table S1 .…”
Section: Methodsmentioning
confidence: 99%
“…The diverse set consisted of 60 spring barley genotypes. The biological status, pedigree information, and population structure have been illustrated [ 90 ]. The list of all genotypes is presented in Table S1 .…”
Section: Methodsmentioning
confidence: 99%
“…Number of genotypes and the efficiency of markers for detecting alleles are relatively determine the PIC values. The PIC mean value was 0.513 which slightly higher than PIC value of 0.36 by Elakhdar et al (2016b), and lower than PIC value of 0.54 by Pasam et al (2014).…”
Section: Resultsmentioning
confidence: 55%
“…In the current study, about 2-8 alleles were detected per a locus with an average of 3.76 alleles (Table 3). This result is greater than 2.6/locus reported by Elakhdar et al (2016b), but lesser than 4 alleles/locus that found by Elakhdar et al (2018), and 6.29 alleles/locus found by Todorovska et al (2019). Size of amplified bands (from 80 to 1200bp) was estimated by comparing the PCR products with the known size of DNA fragments ladder.…”
Section: Resultsmentioning
confidence: 69%
“…Additionally, compared to high throughput molecular markers such as SNPs, SSRs have their own advantages respected to population genetics 62 . The association between SSR markers and abiotic stresses tolerance such as salinity has been recognized and discussed in different plant species 39,63 . One of the main importance of the SSR markers, the inheritance of its alleles from the parents to the progeny which made them an efficient tool in marker-assisted selection breeding programs.…”
Section: Simple Sequence Repeat Analysismentioning
confidence: 99%